Body Matters: Mina Loy and the Art of Intuition - Ellen McWhorter (European Journal of American Studies)
Intuitive knowledge, which is both mysterious and elusive when set against more dominant models of sense-making in the early 20th century, is critical to the representations of love and intimacy in Mina Loy’s famously controversial Love Songs to Joannes. The significance of Loy’s representations of intuition—or the desire to “mean” below the radar—manifests in the discursive antagonisms for which the poem is best known. As Love Songs strains under the weight of two conflicting world views, we come to see that Joannes’s cognitive and individualistic one stands in contrast with the speaker’s intuitive and embodied one. The division between scientific and intuitive modes of knowing occurs within a cultural moment whereby reason and fact came to be aligned with scientific and technological achievement, while being wholly cut off from ordinary human experience and its messier insights. For the speaker of the poem sequence, knowledge about the world gained and presented intuitively, through lived experience and through embodiment, cannot be straightforwardly articulated; for certain experiential truths to be shown at all, they must be made to function beyond the privileged ways of knowing and saying that structured the modern world.